PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT WIDJAJA INDO BERJAYA JAKARTA UTARA - Anisa, Siti; Yunanti, Siska (Journal of Research and Publication Innovation, 2024)
This study of this purpose was to determine the effect of Work Environment and Work Discipline on Employee Performance of PT Widjaja Indo Berjaya North Jakarta Employees Partially and Simultaneously. The research method used is a quantitative method, with the nature of quantitative associative research. The research variables consist of independent variables Work Environment and Work Discipline, and dependent variables Employee Performance. The population taken is as many as 33 respondents. The results of this study indicate that: 1) Work Environment positive affects Employee Performance with regression equation Y=30.853+0.637X1. The value of coefficient determination is 0.579 or 57.9%. Test the hypothesis t count > t table (6.535 > 2.042), then H01 is rejected and Ha1 is accepted. 2) Work Discipline positive effect Employee Performance with regression equation Y=14.308+1.532X2. The value of the coefficient determination is 0.623 or 62.3%. Test the hypothesis t count > t table (7.158 > 2.042), then H02 is rejected and Ha2 is accepted. 3) Work Environment and Work Discipline positively affect Employee Performance with regression equation Y=12.315+0.361X1+0.991X2. The value of the correlation coefficient of 0.866 means the independent variable with the dependent variable has a perfect relationship level a coefficient determination of 0.732 or 73.2%. Test hypothesis F count > F table (40.882 > 3.32), then H03 is rejected and Ha3 is accepted. This means is a significant simultaneously between the Work Environment and Work Discipline on the Performance of PT Widjaja Indo Berjaya North Jakarta Employees.